The political economy of collective skill formation - Busemeyer, Marius R.; Trampusch, Christine (Oxford : Oxford University Press, 2012)
This title examines skill systems and vocational training in a number of coordinated market economies, analysing historical origins and contemporary developments. As well as case studies on Germany, Austria, Switzerland, the Netherlands, and Denmark it also contains comparative chapters exploring reactions to common challenges.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Occupational training; Vocational education